Does postpartum depression predict emotional and cognitive difficulties in 11 year olds? - Maria Elena Komodromou (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This paper examines the role of postpartum depression (PPD) on the emotional and cognitive development of 11-year olds, a key stage of transition in child development before entering adolescence. The present study uses data from the MCS, a longitudinal cohort study with a large and representative sample of the UK population. The results show that PPD impacts on child emotional difficulties when these are reported by the mother or the teacher; child-reported measures of emotional problems do not show any correlation with PPD Cognitive ability tests show no association between PPD and children's cognitive performance at age 11. The results of the paper have enhanced our insight regarding a significant period of transition which has not previously been the focus of research and demonstrate the impact PPD has on children's emotional development.
Keywords: J13; I14; I24; 330; postpartum depression; adolescents; cognitive inequalities; emotional inequalities